The journey back to normality: Support systems and posttrauma needs following exposure to single‐incident trauma among children and adolescents. Issue 1 (2nd January 2023) - Haag, Katharina; Hiller, Rachel; McGuire, Rosie; Lyttle, Mark; Halligan, Sarah L.
Abstract: Social support has been linked to posttrauma adjustment in children and adolescents, but the components of good support remain poorly defined. We conducted qualitative interviews with 30 youths aged 7–16 years after being admitted to a hospital following a single‐incident trauma, predominantly injury or illness. The aim was to identify youths' support needs and examine the support they received across different recovery stages. Thematic analysis revealed that although participants appreciated increased attention and warm support during their hospital stay, most wanted their lives to return to normal soon afterward and were frustrated by barriers to achieving this. Participants received support from different sources, but parents and peers were the most important providers of emotional support and the people with whom these individuals most frequently engaged in trauma‐related conversations. Furthermore, although it was important that schools were sensitive to the youths' potential limitations regarding their ability to engage with lessons, emotional support from teachers was less valued. Overall, this study implies that ecological models incorporating multiple interacting layers capture the structure of youths' posttrauma support systems well. These findings may be used to tailor posttrauma interventions more closely to child and adolescent needs at different recovery stages and highlight the importance of having parents and, where possible, peers involved in posttrauma interventions or prevention programs.